Drug treatment of tricyclic resistant depression - Chalmers, J; Cowen, P (Informa Healthcare, 1990)
The treatment of tricyclic resistant depression is largely empirical because of the lack of clear definition of the term 'resistant depression' and the paucity of controlled trials of this indication. While there is substantial clinical evidence for the efficacy of ECT in tricyclic resistant patients the most established drug treatments are lithium augmentation and monoamine oxidase inhibitor therapy, the latter particularly if the clinical presentation includes features of atypical depression. The combination of neuroleptics and tricyclic treatment is of value in the treatment of depressive psychosis. Several other drug treatments, less well-documented, undoubtedly help some patients. There is a need to establish clinical and biochemical predictors to help identify the likely response of individual patients to particular therapeutic regimes. © 1990 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.